2018
DOI: 10.1242/jeb.186957
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure in the Greenland shark as estimated from ventral aortic elasticity

Abstract: We conducted inflations of freshly excised ventral aortas of the Greenland shark,, and used pressure-diameter data to estimate the point of transition from high to low compliance, which has been shown to occur at the mean blood pressure in other vertebrates including fishes. We also determined the pressure at which the modulus of elasticity of the aorta reached 0.4 MPa, as occurs at the compliance transition in other species. From these analyses, we predict the average ventral aortic blood pressure in to be ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Further evidence of interspecies haplotype sharing has been reported for several juvenile Greenland sharks from the high Arctic that were found to be carrying S. pacificus mtDNA haplotypes (Hussey et al, 2015a). More recently, a full mtDNA genome sequenced with phylogenetic reconstruction placed the Greenland shark and Pacific sleeper shark as sister species with respect to other major shark orders (Santaquiteria et al, 2017). By calibrating the mitogenomic phylogenetic reconstruction with fossil records and geological events, the speciation time of these two species was confirmed to be 3.5 million years ago (mya) (Santaquiteria, 2016;in agreement with Murray et al, 2008).…”
Section: Population Genetics and Genomicsmentioning
confidence: 90%
See 1 more Smart Citation
“…Further evidence of interspecies haplotype sharing has been reported for several juvenile Greenland sharks from the high Arctic that were found to be carrying S. pacificus mtDNA haplotypes (Hussey et al, 2015a). More recently, a full mtDNA genome sequenced with phylogenetic reconstruction placed the Greenland shark and Pacific sleeper shark as sister species with respect to other major shark orders (Santaquiteria et al, 2017). By calibrating the mitogenomic phylogenetic reconstruction with fossil records and geological events, the speciation time of these two species was confirmed to be 3.5 million years ago (mya) (Santaquiteria, 2016;in agreement with Murray et al, 2008).…”
Section: Population Genetics and Genomicsmentioning
confidence: 90%
“…In heart strips that appeared to be contracting normally, a single contraction/relaxation cycle (i.e., a twitch) required 3-5 s to complete at 5 • C, suggesting that maximal heart rate ranges from 12 to 20 beats/min (in agreement with Shiels et al, 2018). While blood pressure in Greenland sharks has never been directly measured, it has been estimated by analyzing the relative amounts of elastin and collagen in the wall of the ventral aorta and measuring its compliance characteristics over a range of pressures (Shadwick et al, 2018). These data suggest that the Greenland shark's average blood pressure is approximately 2.3-2.8 kPa, much lower than other slow swimming sharks, such as the epaulet shark, Hemiscyllium ocellatum (3.9 kPa), or catshark, Scyliorhinus canicula (5.3 kPa), where it has been directly measured (Taylor et al, 1977;Speers-Roesch et al, 2012).…”
Section: Physiological Adaptationsmentioning
confidence: 95%
“…trimethylamine that might be neuroprotective. It is further suggested that Greenland sharks feature a relatively low blood pressure compared to other sharks [18] that might reduce the risk of hypertension-related CNS damage such as stroke or cognitive decline [5]. Up to now, information about genetics from Greenland sharks are largely missing [4,17].…”
mentioning
confidence: 99%